The Impact of QR Codes on Customer Satisfaction For Repurchase Intention on the Basis of Perceived Usefulness, Perceived Ease of Use and Perceived Flow in Food and Beverage Restaurant - Angbawangsa Gabharianza Prawirayudha; Muhammad Arnoldy Syahputera; Raihan Praditya Adisaputra; Rano Kartono Rahim (Riviera Publishing, 2025)
This study explains the analysis of QR code usage in the food and beverage restaurant sector. The purpose of this research is to identify how perceived usefulness, ease of use, and flow experience influence customer satisfaction and repurchase intention. The research employed a quantitative approach by distributing online questionnaires to 385 respondents, with data analyzed using PLS-SEM. The results indicate that perceived usefulness, ease of use, and flow experience positively affect customer satisfaction. Furthermore, customer satisfaction plays an important mediating role in strengthening repurchase intention in restaurants through the use of QR codes.